Civil engineering construction contracts - O'Reilly, Michael (T. Telford ; Distributors for USA, American Society of Civil Engineers, Publications Sales Dept., 1996)
This work provides guidance on all aspects of the most commonly used construction contracts for all those involved in specifying contracts, whether in drafting, administration, claims or dispute resolution. Topics include components of construction contracts, and the tendering process.